Otrokove pravice v Sloveniji - Murgel, Jasna (Pravnik, 2015)
Collection of papers The Rights of the Child in Slovenia, from the normative standards to efficient protection, was published on the 25th anniversary of the Convention of the Rights of the Child by the publishing house Založba FDV and the Ministry of Foreign Affairs of the Republic of Slovenia in December 2014. In the book the authors have presented the Convention on the Rights of the Child and its protocols as well as their implementation in the Slovenian legal system, including the ratification of the third optional protocol to the Convention on the Rights of the Child by the Republic of Slovenia.
Keywords: child; človekove pravice; human rights; mednarodne konvencije; ocene in poročila; otroci; Otrokove pravice v Sloveniji; Slovenia; Slovenija